2010
DOI: 10.1371/journal.pone.0012023
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Management by Private Practitioners in Mumbai, India: Has Anything Changed in Two Decades?

Abstract: SettingMumbai, India. A study conducted in Mumbai two decades ago revealed the extent of inappropriate tuberculosis (TB) management practices of private practitioners. Over the years, India's national TB programme has made significant progress in TB control. Efforts to engage private practitioners have also been made with several successful documented public-private mix initiatives in place.ObjectiveTo study prescribing practices of private practitioners in the treatment of tuberculosis, two decades after a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
164
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(177 citation statements)
references
References 7 publications
4
164
0
Order By: Relevance
“…22 It is therefore very important for the NTP to engage the private sector in TB control. 23 The costs of quality-assured SLDs and monthly culture are usually unaffordable for patients, resulting in treatment interruption and loss to follow-up. Regulating the private sector will be challenging but vital for TB control in the country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 It is therefore very important for the NTP to engage the private sector in TB control. 23 The costs of quality-assured SLDs and monthly culture are usually unaffordable for patients, resulting in treatment interruption and loss to follow-up. Regulating the private sector will be challenging but vital for TB control in the country.…”
Section: Discussionmentioning
confidence: 99%
“…24 Private practitioners should be engaged, trained in NTP guidelines and encouraged to refer DR-TB patients to PMDT sites for treatment. 23 The study had several strengths. It is the first study from Pakistan to examine treatment outcomes among DR-TB patients, and as the study had a large sample size and used routinely collected data, the findings reflect programme realities.…”
Section: Discussionmentioning
confidence: 99%
“…5 Studies from Mumbai and elsewhere have shown poor diagnosis and treatment practices among practitioners in the private health sector that contribute to acquired drug resistance. [6][7][8][9][10] To reduce TB transmission and prevent the emergence of virtually incurable forms of drug-resistant TB, TB management in the private sector must be aligned with the international standards of TB care. [6][7][8][9][10] The involvement of the private sector in India's Revised National TB Control Programme (RNTCP) is therefore crucial.…”
mentioning
confidence: 99%
“…Numerous challenges exist to effectively contain TB drug resistance [3,4,6,13,26]. The WHO policy package to combat antimicrobial drug resistance addresses AMR in a broad sense, but all principles apply fully to TB drug resistance [2,3].…”
mentioning
confidence: 99%
“…The challenge is to ensure that, in all healthcare facilities where TB care is delivered, health workers rigorously follow in routine practice the quality standards that national programmes promote on paper [28]. Importantly, in many countries today, TB drugs are prescribed by private practitioners and inadequate or irregular prescription due to the inability of the patients to buy the drugs and maintain continuity of treatment are leading to development of drug resistance [26]. Therefore, engagement of all health providers is essential, as promoted within the Stop TB Strategy [29].…”
mentioning
confidence: 99%